REITERATION OF LEXICAL COHESION FOUND IN THE SPEECH OF EMMA WATSON’S “GENDER EQUALITY” - Sobandi, Firda Aulia; Syathroh, Isry Laila; Yugafiati, Rasi; Solihat, Solihat (IKIP Siliwangi, 2024)
This study is about the reiteration of lexical cohesion found in Emma Watson’s speech entitled Gender Equality. This study is to find out the types of reiteration in Emma Watson’s speech. The subject of this study is the speech text “Gender Equality” used by Emma Watson for UN Women’s HeForShe campaign. Descriptive qualitative was used as a research method. From the analysis, there are five types of reiteration of lexical cohesion. The result shows that there was 74 reiteration found in total in this study, namely 43 of repetition, 19 of hyponym, 4 of antonym, 5 of synonym, and 3 of superordinate or hypernym. Repetition is the most used in the speech. The reiteration used by Emma Watson in her speech has built up the cohesiveness in the speech of the action of solidarity movement for gender equality to help end the inequalities faced by women globally.